Molecular Modulation of Human α7 Nicotinic Receptor by Amyloid-β Peptides - Lasala, Matías; Fabiani, Camila; Corradi, Jeremías; Antollini, Silvia; Bouzat, Cecilia (Frontiers in Cellular Neuroscience, 2019)
Amyloid β peptide (Aβ) is a key player in the development of Alzheimer’s disease (AD). It is the primary component of senile plaques in AD patients and is also found in soluble forms. Cholinergic activity mediated by α7 nicotinic receptors has been shown to be affected by Aβ soluble forms. To shed light into the molecular mechanism of this effect, we explored the direct actions of oligomeric Aβ1–40 and Aβ1–42 on human α7 by fluorescence spectroscopy and single-channel recordings. Fluorescence measurements using the conformational sensitive probe crystal violet (CrV) revealed that in the presence of Aβ α7 undergoes concentration-dependent conformational changes. Exposure of α7 to 100 pM Aβ changes CrV KD towards that of the desensitized state. However, α7 is still reactive to high carbamylcholine (Carb) concentrations. These observations are compatible with the induction of active/desensitized states as well as of a novel conformational state in the presence of both Aβ and Carb. At 100 nM Aβ, α7 adopts a resting-state-like structure which does not respond to Carb, suggesting stabilization of α7 in a blocked state. In real time, we found that Aβ is capable of eliciting α7 channel activity either in the absence or presence of the positive allosteric modulator (PAM) PNU-120596. Activation by Aβ is favored at picomolar or low nanomolar concentrations and is not detected at micromolar concentrations. At high Aβ concentrations, the mean duration of activation episodes elicited by ACh in the presence of PNU-120596 is significantly reduced, an effect compatible with slow open-channel block. We conclude that Aβ directly affects α7 function by acting as an agonist and a negative modulator. Whereas the capability of low concentrations of Aβ to activate α7 could be beneficial, the reduced α7 activity in the presence of higher Aβ concentrations or its long exposure may contribute to the cholinergic signaling deficit and may be involved in the initiation and development of AD.